Tinjauan Hukum Ketidakpatuhan Rusia Terhadap Provisional Measures International Court Of Justice (ICJ) - Laras Firman Harun; Fence M. Wantu; Mellisa Towadi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This research discusses the Provisional Measure International Court of Justice (ICJ) for Russia's non-compliance in carrying out the decision. The purpose of this study is to determine the legal effectivity and legal consequences of Russia's non-compliance with the Provisonal Measure. The research method used is the normative research method. The outbreak of conflict between Russia and Ukraine This began with the joining of Ukraine and NATO for large-scale air drills in October 2018 which caused Russia's suspicions about its country's security. on February 21, 2022 was triggered by an acknowledgment from the President of Russia, Vladimir Putin on the declaration of independence of Donetsk and Luhanks against Ukraine and in this research discusses the Provisional Measure International Court of Justice (ICJ) for Russia's non-compliance in carrying out the decision. The purpose of this study is to determine the legal effectivity and legal consequences of Russia's non-compliance with the Provisonal Measure. The research method used is the normative research method. The outbreak of conflict between Russia and Ukraine This began with the joining of Ukraine and NATO for large-scale air drills in October 2018 which caused Russia's suspicions about its country's security. on February 21, 2022 was triggered by the recognition of the President of Russia, Vladimir Putin on the declaration of independence of Donetsk and Luhanks against Ukraine and on February 24, 2022 Russia announced a special military operation in Ukraine with the aim of demilitarization and denazification and has no orientation to occupy Ukraine .Therefore, Ukraine took steps to oppose Russia in the International Court of Justice (ICJ) with the result of the Provisional Measures. Russia must suspend military operations and refrain from any action that worsens the situation. Russia however rejects the Court's Jurisdiction claiming it does not apply the Genocide Covenant and argues Ar. 51 The United Nations charter of self-defense argued that the Ukrainian application was invalid and the case should be dismissed because Ar.51 is not ICJ Jurisdiction. Even though Article 41 of the International Statute states that